Agam Regency Toddlers Stunting Incidents From 2018 to 2022 - Octaferina, Rahmi; Gusti, Aria; Masrizal, Masrizal (LPPM Universitas Prima Nusantara Bukittinggi, 2023)
Background: Stunting is a dietary problem that can have negative effects on IQ, raise the likelihood of non-communicable diseases, and impede future output. According to the findings of the 2022 SSGI, the occurrence of stunting in Agam Regency is 24.6%, surpassing the national occurrence of just 21.6%.Objective: The purpose of this study is to ascertain the prevalence of stunting in toddlers and provide a geographical representation of Agam Regency from 2018 to 2022.Method: This study employed an ecological approach, utilizing secondary data obtained from the health profiles and nutritional reports of the Agam Regency Health Department spanning the years 2018 to 2022. The study sample comprised of young children who have undergone stunting in Agam Regency during the years 2018 and 2022. The sample selection employed the total sampling technique.The analysis encompassed both univariate and spatial analysis techniques.Result: The univariate analysis shows that the occurrence of stunting increased in 2020 and then decreased from 2021 to 2022. The highest frequency in 2018 was documented at a rate of 28 per 100 youngsters. The Agam District Health Service should improve cooperation with many initiatives and interconnected sectors relating to environmental health.